Preparation method of anti-shedding hydrogel dressing
By blending sodium carboxymethyl cellulose fiber and polyester fiber into nonwoven fabric, and through acidification treatment and cross-linking reaction, the bonding force between hydrogel and nonwoven fabric is enhanced, solving the problem of easy fall-off of traditional hydrogel dressings, and realizing the preparation of hydrogel dressings with high bonding force.
Patent Information
- Application Number
- CN202411486669.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional hydrogel dressings have insufficient adhesion to non-woven fabrics, causing the hydrogel to easily detach from the non-woven fabric and affecting the effectiveness of the treatment.
Nonwoven fabric is made by blending sodium carboxymethyl cellulose fiber and polyester fiber, and modified nonwoven fabric is formed by acidification treatment. Combined with hydrogel coating process, the cross-linking reaction of carboxymethyl cellulose hydrogen fiber and aluminum hydroxyl cross-linking agent is used to enhance the bonding force.
It improves the bonding strength between hydrogel and modified nonwoven fabric, with a peel force of 5.3–7.8 N, extending service life and simplifying the production process.
Smart Images

Figure CN119280468A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical dressings, and in particular relates to a method for preparing an anti-shedding hydrogel dressing. Background Art
[0002] With the advancement of medical technology, medical materials have also shifted from traditional gauze dressings to new dressings, among which hydrogel dressings are the most widely used. Hydrogel dressings mainly include hydrogels and non-woven fabrics. Hydrogels have good biocompatibility and a unique three-dimensional network structure. They swell in water but do not dissolve. They can absorb and retain a large amount of moisture, and can keep the wound surface moist when applied to the wound.
[0003] The non-woven fabrics of traditional hydrogel dressings are mostly TPU non-woven fabrics, polyester fiber non-woven fabrics, etc., which can be used as carriers of hydrogels and are more convenient to use. However, hydrogels can absorb more than ten times their own weight in water, and the load capacity of non-woven fabrics is insufficient. Therefore, it is difficult for hydrogels to be firmly bonded to non-woven fabrics and they are easy to fall off from the non-woven fabrics, affecting their use. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a method for preparing an anti-shedding hydrogel dressing, thereby achieving the invention purpose of improving the bonding strength between non-woven fabric and hydrogel.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing an anti-shedding hydrogel dressing comprises the following steps: S1. Preparation of nonwoven fabric Sodium carboxymethyl cellulose fiber and polyester fiber are blended into mixed fibers, which are then opened, evenly laid, needle-punched and compacted to form non-woven fabrics.
[0006] Preferably, the linear density of the sodium carboxymethyl cellulose fiber is 0.5 to 2 dtex, and the length is 2 to 8 cm; the linear density of the polyester fiber is 0.5 to 2 dtex, and the length is 2 to 8 cm.
[0007] Preferably, the mass fraction of sodium carboxymethyl cellulose fiber in the mixed fiber is 13-100%, and the rest is polyester fiber.
[0008] Preferably, the nonwoven fabric has a gram weight of 60 to 90 g / m 2 .
[0009] S2, acidification The nonwoven fabric is immersed in an acid composite solution for acid treatment, and the sodium of the sodium carboxymethyl cellulose fiber is removed to obtain a modified nonwoven fabric containing hydrogen carboxymethyl cellulose fiber, sodium carboxymethyl cellulose fiber and polyester fiber.
[0010] Preferably, in terms of mass fraction, the alcohol in the acid composite solution accounts for 65-75%, the acid accounts for 1-4.5%, and the rest is water. Sodium carboxymethyl cellulose fiber is soluble in water, so in order to prevent the sodium carboxymethyl cellulose fiber from dissolving, the alcohol concentration in the acid composite solution should be greater than 65%; but too high an alcohol concentration will hinder sodium removal, and the alcohol preferably accounts for 65-75%.
[0011] Preferably, the alcohol is one or more of methanol, ethanol and isopropanol.
[0012] Preferably, the acid is one or more of acetic acid and hydrochloric acid.
[0013] Preferably, the acidification treatment time is 4 to 24 hours.
[0014] Preferably, the mass ratio of the non-woven fabric to the acid composite solution is 1:5-20.
[0015] Preferably, the mass fraction of sodium carboxymethyl cellulose fibers in the modified nonwoven fabric is 3-35%, the mass fraction of hydrogen carboxymethyl cellulose fibers is 10-65%, and the rest are polyester fibers.
[0016] S3. Preparation of hydrogel Add glycerol and partially neutralized sodium polyacrylate into a blender and stir evenly to obtain an oil phase; add water, tartaric acid, aluminum glycolate crosslinker and disodium ethylenediaminetetraacetate into a blender and stir, and after stirring, let stand to defoam to obtain an aqueous phase; add the oil phase into the aqueous phase and stir to mix the two, then continue stirring under vacuum for 5 to 8 minutes, release the vacuum, discharge the mixture of the oil phase and the aqueous phase, and let stand for 5 to 8 hours to obtain a hydrogel.
[0017] Preferably, the agitator is a vacuum double planetary power agitator, and the stirring time is 10 to 20 minutes.
[0018] Preferably, the vacuum degree of the vacuum condition is 0.05-0.15 MPa.
[0019] Preferably, in parts by weight, the glycerol is 21 to 23 parts, the partially neutralized sodium polyacrylate is 5 to 6 parts, the water is 70 to 75 parts, the tartaric acid is 0.22 to 0.25 parts, the aluminum glycolate crosslinking agent is 0.1 to 0.13 parts, and the disodium ethylenediaminetetraacetic acid is 0.1 to 0.13 parts.
[0020] S4. Cross-linking The modified nonwoven fabric is arranged in a coating device; the hydrogel is transported to the coating device, coated on the modified nonwoven fabric, and then subjected to a curing treatment to obtain a hydrogel dressing.
[0021] Preferably, the coating thickness is 0.5 to 7 mm; and the aging treatment time is 8 to 24 hours.
[0022] The modified non-woven fabric contains sodium carboxymethyl cellulose fiber, carboxymethyl cellulose hydrogen fiber and polyester fiber. After the hydrogel is coated on the modified non-woven fabric, the unreacted aluminum glycolate crosslinking agent in the hydrogel contacts the modified non-woven fabric, and tartaric acid provides an acidic environment. A cross-linking reaction occurs between the partially neutralized sodium polyacrylate in the hydrogel, the carboxymethyl cellulose hydrogen fiber in the modified non-woven fabric and the aluminum glycolate crosslinking agent, and the bonding force between the hydrogel and the modified non-woven fabric is enhanced.
[0023] Since the sodium carboxymethyl cellulose fibers in the modified nonwoven fabric are soluble in water, in order to avoid the coating of the hydrogel from damaging the bonding strength performance of the modified nonwoven fabric, the proportion of the sodium carboxymethyl cellulose fibers in the modified nonwoven fabric is less than 35%, preferably 3-35%.
[0024] Due to the adoption of the above technical solution, the technical effects achieved by the present invention are: 1. The hydrogel dressing prepared by the present invention is easy to use, and the hydrogel has good bonding strength with the modified non-woven fabric, is not easy to fall off from the surface of the modified non-woven fabric, and has a prolonged service life.
[0025] 2. The bonding strength between the hydrogel and the modified non-woven fabric of the hydrogel dressing prepared by the present invention is high, and the peeling force is 5.3-7.8N.
[0026] 3. The present invention prepares non-woven fabrics from sodium carboxymethyl cellulose fibers and polyester fibers, and obtains modified non-woven fabrics containing carboxymethyl cellulose hydrogen fibers, sodium carboxymethyl cellulose fibers and polyester fibers after acidification and sodium removal. The modified non-woven fabrics contain sodium carboxymethyl cellulose fibers, carboxymethyl cellulose hydrogen fibers and polyester fibers. After the hydrogel is coated on the modified non-woven fabrics, the unreacted aluminum glycolate crosslinking agent in the hydrogel contacts the modified non-woven fabrics, and tartaric acid provides an acidic environment. Cross-linking reaction occurs between the partially neutralized sodium polyacrylate in the hydrogel, the carboxymethyl cellulose hydrogen fibers in the modified non-woven fabrics and the aluminum glycolate crosslinking agent, and the bonding force between the hydrogel and the modified non-woven fabrics is enhanced, thereby achieving the purpose of preventing shedding. The process is simple and can be put into large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the peeling of the hydrogel dressing of the present invention. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific embodiments.
[0029] Example 1 S1. Preparation of nonwoven fabric Sodium carboxymethyl cellulose fiber and polyester fiber are blended into mixed fibers, which are then opened, evenly laid, needle-punched and compacted to form non-woven fabrics.
[0030] The linear density of the sodium carboxymethyl cellulose fiber is 1 dtex, and the length is 6 cm; the linear density of the polyester fiber is 1 dtex, and the length is 6 cm.
[0031] The mass fraction of sodium carboxymethyl cellulose fiber in the mixed fiber is 60%, and the rest is polyester fiber.
[0032] The nonwoven fabric has a gram weight of 80 g / m 2 .
[0033] S2, acidification The nonwoven fabric is immersed in an acid composite solution for acid treatment, and the sodium of the sodium carboxymethyl cellulose fiber is removed to obtain a modified nonwoven fabric containing hydrogen carboxymethyl cellulose fiber, sodium carboxymethyl cellulose fiber and polyester fiber.
[0034] In terms of mass fraction, the acid composite solution comprises 70% alcohol, 2.5% acid and the rest water.
[0035] The alcohol is ethanol, and the acid is acetic acid.
[0036] The acidification treatment time is 24h.
[0037] The mass ratio of the non-woven fabric to the acid composite solution is 1:12.
[0038] The mass fraction of sodium carboxymethyl cellulose fiber in the modified non-woven fabric is 10%, the mass fraction of hydrogen carboxymethyl cellulose fiber is 50%, and the rest is polyester fiber.
[0039] S3. Preparation of hydrogel Add glycerol and partially neutralized sodium polyacrylate into a blender and stir evenly to obtain an oil phase; add water, tartaric acid, aluminum glycolate crosslinker and disodium ethylenediaminetetraacetate into a blender and stir, and after stirring, let stand to defoam to obtain an aqueous phase; add the oil phase into the aqueous phase and stir to mix the two, then continue stirring under vacuum for 7 minutes, release the vacuum, discharge the mixture of the oil phase and the aqueous phase, and let stand for 7 hours to obtain a hydrogel.
[0040] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 15 minutes.
[0041] The vacuum degree of the vacuum condition is 0.1 MPa.
[0042] In terms of weight parts, the glycerol is 22 parts, the partially neutralized sodium polyacrylate is 5.5 parts, the water is 73 parts, the tartaric acid is 0.23 parts, the aluminum glycolate crosslinking agent is 0.12 parts, and the disodium ethylenediaminetetraacetic acid is 0.12 parts.
[0043] S4. Cross-linking The modified nonwoven fabric is arranged in a coating device; the hydrogel is transported to the coating device, coated on the modified nonwoven fabric, and then subjected to a curing treatment to obtain a hydrogel dressing.
[0044] The coating thickness is 2.5 mm; the aging treatment time is 16 h.
[0045] Example 2 S1. Preparation of nonwoven fabric Sodium carboxymethyl cellulose fiber and polyester fiber are blended into mixed fibers, which are then opened, evenly laid, needle-punched and compacted to form non-woven fabrics.
[0046] The linear density of the sodium carboxymethyl cellulose fiber is 0.5 dtex, and the length is 2 cm; the linear density of the polyester fiber is 0.5 dtex, and the length is 2 cm.
[0047] The mass fraction of sodium carboxymethyl cellulose fiber in the mixed fiber is 13%, and the rest is polyester fiber.
[0048] The nonwoven fabric has a grammage of 60 g / m 2 .
[0049] S2, acidification The nonwoven fabric is immersed in an acid composite solution for acid treatment, and the sodium of the sodium carboxymethyl cellulose fiber is removed to obtain a modified nonwoven fabric containing hydrogen carboxymethyl cellulose fiber, sodium carboxymethyl cellulose fiber and polyester fiber.
[0050] In terms of mass fraction, the acid composite solution comprises 65% alcohol, 1% acid and the rest water.
[0051] The alcohol is methanol, and the acid is acetic acid.
[0052] The acidification treatment time is 12h.
[0053] The mass ratio of the non-woven fabric to the acid composite solution is 1:5.
[0054] The mass fraction of sodium carboxymethyl cellulose fiber in the modified nonwoven fabric is 3%, the mass fraction of hydrogen carboxymethyl cellulose fiber is 10%, and the rest is polyester fiber.
[0055] S3. Preparation of hydrogel Add glycerol and partially neutralized sodium polyacrylate into a blender and stir evenly to obtain an oil phase; add water, tartaric acid, aluminum glycolate crosslinker and disodium ethylenediaminetetraacetate into a blender and stir, and after stirring, let stand to defoam to obtain an aqueous phase; add the oil phase into the aqueous phase and stir to mix the two, then continue stirring under vacuum for 5 minutes, release the vacuum, discharge the mixture of the oil phase and the aqueous phase, and let stand for 5 hours to obtain a hydrogel.
[0056] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 10 minutes.
[0057] The vacuum degree of the vacuum condition is 0.05 MPa.
[0058] In terms of weight parts, the glycerol is 21 parts, the partially neutralized sodium polyacrylate is 5 parts, the water is 70 parts, the tartaric acid is 0.22 parts, the aluminum glycolate crosslinking agent is 0.1 parts, and the disodium ethylenediaminetetraacetic acid is 0.1 parts.
[0059] S4. Cross-linking The modified nonwoven fabric is arranged in a coating device; the hydrogel is transported to the coating device, coated on the modified nonwoven fabric, and then subjected to a curing treatment to obtain a hydrogel dressing.
[0060] The coating thickness is 0.5 mm; the aging treatment time is 8 h.
[0061] Example 3 S1. Preparation of nonwoven fabric Sodium carboxymethyl cellulose fibers are mixed into mixed fibers, which are then opened, evenly laid, needle-punched, and compacted to form non-woven fabrics.
[0062] The linear density of the sodium carboxymethyl cellulose fiber is 2 dtex and the length is 8 cm.
[0063] The nonwoven fabric has a gram weight of 90 g / m 2 .
[0064] S2, acidification The nonwoven fabric is immersed in an acid composite solution for acid treatment, and the sodium carboxymethyl cellulose fibers are de-sodiumized to obtain a modified nonwoven fabric containing carboxymethyl cellulose hydrogen fibers and sodium carboxymethyl cellulose fibers.
[0065] In terms of mass fraction, the acid composite solution comprises 75% alcohol, 4.5% acid and the rest water.
[0066] The alcohol is methanol, and the acid is hydrochloric acid.
[0067] The acidification treatment time is 4 hours.
[0068] The mass ratio of the non-woven fabric to the acid composite solution is 1:20.
[0069] The mass fraction of sodium carboxymethyl cellulose fibers in the modified nonwoven fabric is 35%, and the mass fraction of hydrogen carboxymethyl cellulose fibers is 65%.
[0070] S3. Preparation of hydrogel Add glycerol and partially neutralized sodium polyacrylate into a blender and stir evenly to obtain an oil phase; add water, tartaric acid, aluminum glycolate crosslinker and disodium ethylenediaminetetraacetate into a blender and stir, and after stirring, let stand to defoam to obtain an aqueous phase; add the oil phase into the aqueous phase and stir to mix the two, then continue stirring under vacuum for 8 minutes, release the vacuum, discharge the mixture of the oil phase and the aqueous phase, and let stand for 8 hours to obtain a hydrogel.
[0071] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 20 minutes.
[0072] The vacuum degree of the vacuum condition is 0.15 MPa.
[0073] In terms of weight, the glycerol is 23 parts, the partially neutralized sodium polyacrylate is 6 parts, the water is 75 parts, the tartaric acid is 0.25 parts, the aluminum glycolate crosslinking agent is 0.13 parts, and the disodium ethylenediaminetetraacetic acid is 0.13 parts.
[0074] S4. Cross-linking The modified nonwoven fabric is arranged in a coating device; the hydrogel is transported to the coating device, coated on the modified nonwoven fabric, and then subjected to a curing treatment to obtain a hydrogel dressing.
[0075] The coating thickness is 7 mm; the aging time is 24 h.
[0076] Example 4 S1. Preparation of nonwoven fabric Sodium carboxymethyl cellulose fiber and polyester fiber are blended into mixed fibers, which are then opened, evenly laid, needle-punched and compacted to form non-woven fabrics.
[0077] The linear density of the sodium carboxymethyl cellulose fiber is 1 dtex, and the length is 6 cm; the linear density of the polyester fiber is 1 dtex, and the length is 6 cm.
[0078] The mass fraction of sodium carboxymethyl cellulose fiber in the mixed fiber is 50%, and the rest is polyester fiber.
[0079] The nonwoven fabric has a gram weight of 80 g / m 2 .
[0080] S2, acidification The nonwoven fabric is immersed in an acid composite solution for acid treatment, and the sodium of the sodium carboxymethyl cellulose fiber is removed to obtain a modified nonwoven fabric containing hydrogen carboxymethyl cellulose fiber, sodium carboxymethyl cellulose fiber and polyester fiber.
[0081] In terms of mass fraction, the acid composite solution comprises 70% alcohol, 2.5% acid and the rest water.
[0082] The alcohol is ethanol, and the acid is acetic acid.
[0083] The acidification treatment time is 12h.
[0084] The mass ratio of the non-woven fabric to the acid composite solution is 1:12.
[0085] The mass fraction of sodium carboxymethyl cellulose fiber in the modified nonwoven fabric is 20%, the mass fraction of hydrogen carboxymethyl cellulose fiber is 30%, and the rest is polyester fiber.
[0086] S3. Preparation of hydrogel Add glycerol and partially neutralized sodium polyacrylate into a blender and stir evenly to obtain an oil phase; add water, tartaric acid, aluminum glycolate crosslinker and disodium ethylenediaminetetraacetate into a blender and stir, and after stirring, let stand to defoam to obtain an aqueous phase; add the oil phase into the aqueous phase and stir to mix the two, then continue stirring under vacuum for 7 minutes, release the vacuum, discharge the mixture of the oil phase and the aqueous phase, and let stand for 7 hours to obtain a hydrogel.
[0087] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 15 minutes.
[0088] The vacuum degree of the vacuum condition is 0.1 MPa.
[0089] In terms of weight parts, the glycerol is 22 parts, the partially neutralized sodium polyacrylate is 5.5 parts, the water is 73 parts, the tartaric acid is 0.23 parts, the aluminum glycolate crosslinking agent is 0.12 parts, and the disodium ethylenediaminetetraacetic acid is 0.12 parts.
[0090] S4. Cross-linking The modified nonwoven fabric is arranged in a coating device; the hydrogel is transported to the coating device, coated on the modified nonwoven fabric, and then subjected to a curing treatment to obtain a hydrogel dressing.
[0091] The coating thickness is 2.5 mm; the aging treatment time is 16 h.
[0092] Example 5 S1. Preparation of nonwoven fabric Sodium carboxymethyl cellulose fiber and polyester fiber are blended into mixed fibers, which are then opened, evenly laid, needle-punched and compacted to form non-woven fabrics.
[0093] The linear density of the sodium carboxymethyl cellulose fiber is 1 dtex, and the length is 6 cm; the linear density of the polyester fiber is 1 dtex, and the length is 6 cm.
[0094] The mass fraction of sodium carboxymethyl cellulose fiber in the mixed fiber is 60%, and the rest is polyester fiber.
[0095] The nonwoven fabric has a gram weight of 80 g / m 2 .
[0096] S2, acidification The nonwoven fabric is immersed in an acid composite solution for acid treatment, and the sodium of the sodium carboxymethyl cellulose fiber is removed to obtain a modified nonwoven fabric containing hydrogen carboxymethyl cellulose fiber, sodium carboxymethyl cellulose fiber and polyester fiber.
[0097] In terms of mass fraction, the acid composite solution comprises 70% alcohol, 2.5% acid and the rest water.
[0098] The alcohol is ethanol, and the acid is acetic acid.
[0099] The acidification treatment time is 12h.
[0100] The mass ratio of the non-woven fabric to the acid composite solution is 1:12.
[0101] The mass fraction of sodium carboxymethyl cellulose fiber in the modified non-woven fabric is 10%, the mass fraction of hydrogen carboxymethyl cellulose fiber is 50%, and the rest is polyester fiber.
[0102] S3. Preparation of hydrogel Add glycerol and partially neutralized sodium polyacrylate into a blender and stir evenly to obtain an oil phase; add water, tartaric acid, aluminum glycolate crosslinker and disodium ethylenediaminetetraacetate into a blender and stir, and after stirring, let stand to defoam to obtain an aqueous phase; add the oil phase into the aqueous phase and stir to mix the two, then continue stirring under vacuum for 7 minutes, release the vacuum, discharge the mixture of the oil phase and the aqueous phase, and let stand for 7 hours to obtain a hydrogel.
[0103] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 15 minutes.
[0104] The vacuum degree of the vacuum condition is 0.1 MPa.
[0105] In terms of weight parts, the glycerol is 22 parts, the partially neutralized sodium polyacrylate is 5.5 parts, the water is 73 parts, the tartaric acid is 0.23 parts, the aluminum glycolate crosslinking agent is 0.12 parts, and the disodium ethylenediaminetetraacetic acid is 0.12 parts.
[0106] S4. Cross-linking The modified nonwoven fabric is arranged in a coating device; the hydrogel is transported to the coating device, coated on the modified nonwoven fabric, and then subjected to a curing treatment to obtain a hydrogel dressing.
[0107] The coating thickness is 0.5 mm; the aging treatment time is 8 h.
[0108] Example 6 S1. Preparation of nonwoven fabric Sodium carboxymethyl cellulose fiber and polyester fiber are blended into mixed fibers, which are then opened, evenly laid, needle-punched and compacted to form non-woven fabrics.
[0109] The linear density of the sodium carboxymethyl cellulose fiber is 1 dtex, and the length is 6 cm; the linear density of the polyester fiber is 1 dtex, and the length is 6 cm.
[0110] The mass fraction of sodium carboxymethyl cellulose fiber in the mixed fiber is 60%, and the rest is polyester fiber.
[0111] The nonwoven fabric has a gram weight of 80 g / m 2 .
[0112] S2, acidification The nonwoven fabric is immersed in an acid composite solution for acid treatment, and the sodium of the sodium carboxymethyl cellulose fiber is removed to obtain a modified nonwoven fabric containing hydrogen carboxymethyl cellulose fiber, sodium carboxymethyl cellulose fiber and polyester fiber.
[0113] In terms of mass fraction, the acid composite solution comprises 70% alcohol, 2.5% acid and the rest water.
[0114] The alcohol is ethanol, and the acid is acetic acid.
[0115] The acidification treatment time is 12h.
[0116] The mass ratio of the non-woven fabric to the acid composite solution is 1:12.
[0117] The mass fraction of sodium carboxymethyl cellulose fiber in the modified non-woven fabric is 10%, the mass fraction of hydrogen carboxymethyl cellulose fiber is 50%, and the rest is polyester fiber.
[0118] S3. Preparation of hydrogel Add glycerol and partially neutralized sodium polyacrylate into a blender and stir evenly to obtain an oil phase; add water, tartaric acid, aluminum glycolate crosslinker and disodium ethylenediaminetetraacetate into a blender and stir, and after stirring, let stand to defoam to obtain an aqueous phase; add the oil phase into the aqueous phase and stir to mix the two, then continue stirring under vacuum for 7 minutes, release the vacuum, discharge the mixture of the oil phase and the aqueous phase, and let stand for 7 hours to obtain a hydrogel.
[0119] The stirrer is a vacuum double planetary power stirrer, and the stirring time is 15 minutes.
[0120] The vacuum degree of the vacuum condition is 0.1 MPa.
[0121] In terms of weight parts, the glycerol is 22 parts, the partially neutralized sodium polyacrylate is 5.5 parts, the water is 73 parts, the tartaric acid is 0.23 parts, the aluminum glycolate crosslinking agent is 0.12 parts, and the disodium ethylenediaminetetraacetic acid is 0.12 parts.
[0122] S4. Cross-linking The modified nonwoven fabric is arranged in a coating device; the hydrogel is transported to the coating device, coated on the modified nonwoven fabric, and then subjected to a curing treatment to obtain a hydrogel dressing.
[0123] The coating thickness is 7 mm; the aging time is 24 h.
[0124] Comparative Example 1 Representative Example 1 was selected, and the sodium carboxymethyl cellulose fiber in the non-woven fabric and step S2 were removed, and the rest were consistent with Example 1, as Comparative Example 1.
[0125] Comparative Example 2 The representative Example 1 was selected, and the acidification conditions for sodium removal in S2 and the proportion of sodium carboxymethyl cellulose fibers in the non-woven fabric were adjusted. The mass fraction of sodium carboxymethyl cellulose fibers in the modified non-woven fabric finally obtained was 40%, the mass fraction of carboxymethyl cellulose hydrogen fibers was 30%, and the rest were polyester fibers; the rest were consistent with Example 1, as Comparative Example 2.
[0126] The hydrogel dressings prepared in the examples and comparative examples were subjected to a peeling test. The test method was as follows: the hydrogel dressing was made into a sample with a size of 15 mm × 40 mm, and the hydrogel surface and the modified non-woven fabric surface of the sample were clamped with a clamp, and the clamping part could not slip, so as to ensure that the applied tension was evenly distributed over the width of the sample. The test machine was started, and the upper and lower clamps were separated at a rate of 100 + 10 mm / min. The sample peeling length was at least 125 mm, and the recording device simultaneously drew the peeling load curve until the bonding surface between the glue surface and the modified non-woven fabric was destroyed. The specific results are shown in Table 1.
[0127] Table 1 Test items Peel force (N) Example 1 6.4 Example 2 5.3 Example 3 5.8 Example 4 6.1 Example 5 5.6 Example 6 7.8 Comparative Example 1 2 Comparative Example 2 2.9 It can be seen from Table 1 that the amount of sodium carboxymethyl cellulose fiber and carboxymethyl cellulose hydrogen fiber in the modified nonwoven fabric and the thickness of the hydrogel have a greater influence on the tear strength of the hydrogel, and the amount of sodium carboxymethyl cellulose fiber and carboxymethyl cellulose hydrogen fiber in the modified nonwoven fabric is controlled by the acidification step.
[0128] Comparative Example 1 only uses polyester fibers, and the bonding ability between the hydrogel and the non-woven fabric is poor. The tear strength of Example 1 is much greater than that of Comparative Example 1, indicating that the modified non-woven fabric contains sodium carboxymethyl cellulose fibers, carboxymethyl cellulose hydrogen fibers and polyester fibers. After the hydrogel is coated on the modified non-woven fabric, the unreacted aluminum glycolate crosslinking agent in the hydrogel contacts the modified non-woven fabric, and tartaric acid provides an acidic environment. A cross-linking reaction occurs between the partially neutralized sodium polyacrylate in the hydrogel, the carboxymethyl cellulose hydrogen fibers in the modified non-woven fabric, and the aluminum glycolate crosslinking agent, and the bonding force between the hydrogel and the modified non-woven fabric is enhanced.
[0129] In Comparative Example 2, the mass fraction of sodium carboxymethyl cellulose fiber in the modified non-woven fabric is 40%, the mass fraction of carboxymethyl cellulose hydrogen fiber is 30%, and the rest is polyester fiber. The tear strength also decreases. This is because the sodium carboxymethyl cellulose fiber in the modified non-woven fabric is soluble in water. If the proportion of sodium carboxymethyl cellulose fiber is too high, it will have a certain impact on the performance of the modified non-woven fabric, and then affect the bonding strength between the hydrogel and the modified non-woven fabric.
[0130] Unless otherwise specified, the ratios and percentages described in the present invention are all weight ratios and weight percentages; and the raw materials are all commercially available.
[0131] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an anti-shedding hydrogel dressing, characterized in that: The preparation method comprises the preparation of non-woven fabric, acidification, preparation of hydrogel and cross-linking.
2. The method for preparing an anti-shedding hydrogel dressing according to claim 1, characterized in that: The non-woven fabric is prepared by blending sodium carboxymethyl cellulose fiber and polyester fiber into mixed fibers, and then opening, evenly laying, needle punching and compacting the mixed fibers to form the non-woven fabric.
3. The method for preparing an anti-shedding hydrogel dressing according to claim 2, characterized in that: The linear density of the sodium carboxymethyl cellulose fiber is 0.5-2 dtex, and the length is 2-8 cm; the linear density of the polyester fiber is 0.5-2 dtex, and the length is 2-8 cm; The mass fraction of sodium carboxymethyl cellulose fiber in the mixed fiber is 13-100%, and the rest is polyester fiber; The nonwoven fabric has a gram weight of 60 to 90 g / m 2 .
4. The method for preparing an anti-shedding hydrogel dressing according to claim 1, characterized in that: The acidification is to immerse the nonwoven fabric in an acid composite solution for acidification treatment, remove sodium from the sodium carboxymethyl cellulose fibers, and obtain a modified nonwoven fabric containing hydrogen carboxymethyl cellulose fibers, sodium carboxymethyl cellulose fibers and polyester fibers.
5. The method for preparing an anti-shedding hydrogel dressing according to claim 4, characterized in that: In terms of mass fraction, the alcohol in the acid composite solution accounts for 65-75%, the acid accounts for 1-4.5%, and the rest is water; The acidification treatment time is 4 to 24 hours; The mass ratio of the non-woven fabric to the acid composite solution is 1:5-20.
6. The method for preparing an anti-shedding hydrogel dressing according to claim 4, characterized in that: The mass fraction of sodium carboxymethyl cellulose fiber in the modified nonwoven fabric is 3-35%, the mass fraction of hydrogen carboxymethyl cellulose fiber is 10-65%, and the rest is polyester fiber.
7. The method for preparing an anti-shedding hydrogel dressing according to claim 1, characterized in that: The preparation of the hydrogel comprises the following steps: adding glycerol and partially neutralized sodium polyacrylate into a stirrer and stirring evenly to obtain an oil phase; adding water, tartaric acid, aluminum glycolate crosslinking agent and disodium ethylenediaminetetraacetate into the stirrer and stirring, and standing to defoam after the stirring is completed to obtain an aqueous phase; adding the oil phase into the aqueous phase and stirring to mix the two, and then continuing to stir for 5 to 8 minutes under vacuum conditions, releasing the vacuum, discharging the mixture of the oil phase and the aqueous phase, and standing for 5 to 8 hours to obtain a hydrogel; The stirrer is a vacuum double planetary power stirrer, and the stirring time is 10 to 20 minutes; Preferably, the vacuum degree of the vacuum condition is 0.05-0.15 MPa.
8. The method for preparing an anti-shedding hydrogel dressing according to claim 7, characterized in that: In terms of weight, the glycerol is 21 to 23 parts, the partially neutralized sodium polyacrylate is 5 to 6 parts, the water is 70 to 75 parts, the tartaric acid is 0.22 to 0.25 parts, the aluminum glycolate crosslinking agent is 0.1 to 0.13 parts, and the disodium ethylenediaminetetraacetic acid is 0.1 to 0.13 parts.
9. The method for preparing an anti-shedding hydrogel dressing according to claim 1, characterized in that: The cross-linking is as follows: placing the modified non-woven fabric in a coating device; conveying the hydrogel to the coating device, coating the modified non-woven fabric, and then subjecting the coating to a aging treatment to obtain a hydrogel dressing.
10. The method for preparing an anti-shedding hydrogel dressing according to claim 9, characterized in that: The coating thickness is 0.5 to 7 mm; the aging treatment time is 8 to 24 hours.